THE NEW MELATONIN DERVATIVE, ITS SOME BIOLOGICAL ACTIVITIES AND HPLC APPLICATION - AL-NABAWI, SRWA HASHIM MOHAMMED (Fırat Üniveristesi, 2019)
Bu çalışmada, yeni melatonin türevi sentezlendi ve bu bileşiğin biyolojik özellikleri ile birlikte HPLC-UV ile analizi için metot geliştirme amaçlandı. İlk olarak, benzil klorür ile bileşiğin yeni türevi sentezlendi. Yeni türevin saflığı erime noktası ile, yapısı ise IR, 1H NMR and 13C-NMR ve elemental analiz teknikleri ile aydınlatıldı. Ikinci olarak, antimikrobiyal ve antioksidan özellikleri farklı mikroorganizmalar ve antioksidan yöntemler kullanılarak belirlendi. Üçüncü olarak, yeni bileşiğin HPLC-UV ile analizi için metot geliştirildi.

In this study, it is aimed to synthesize a new derivative of melatonin and evaluate the biological properties of this new derivative as well as to develop a new method for analyzing HPLC. In the first step, the new derivative of this compound was prepared with benzyl chloride. The purity control of the obtained derivative was made by means of melting point and the chemical structure was confirmed by IR, 1H NMR and 13C-NMR spectral analyses and results with elemental analysis were supported. In the second step, antimicrobial and antioxidant properties of synthesized melatonin derivative were investigated using different microorganism and antioxidant methods. In the last step, the method for the analysis of the new derivative in biological sample by HPLC-UV was developed.
Yeni melatonin türevi, bazı biyolojik aktiviteleri ve HPLC uygulamaları
Keywords: Biyokimya; Kimya